ANALISIS KEPASTIAN SUMBER HUKUM PEMIDANAAN TERHADAP DELIK ABORSI DALAM SISTEM PERADILAN PIDANA (STUDI PUTUSAN PENGADILAN TINGGI JAMBI NOMOR 6/PID.SUS-ANAK/2018) - Rosita Rosita; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2021)
The discussion articulated in this research material is on the subject of uncertainty of legal source relating to passing of sentencingin cases involving abortion offense under the criminal justice system (as applied in the Jambi High Court Decision Number 6/Pid.Sus-Anak /2018) and the Court’s application on sentencing for such offenses. The primary material used for this research analysis is juridical normative, therefore the sources of data used by the author is primary data fromlaws and regulations, including positive Indonesian law, secondary data from literature studies and various literatures and tertiary data, namely, dictionaries, media and encyclopedias. The materials and data were collected from research conducted from well-equipped legal libraries / authorities. The judge's decision purporting that the perpetrator is held free from abortion offense in cases involving rape victims is somewhat ambiguousunder the existing Criminal Code and Laws, and this ambiguity should be analyzed in the light of law Number 36 of 2009 which concerns health and specifically under Indonesian positive law which adheres to the doctrine of “lex specialis derogat legi generalis” (“special law repeals general laws”). In addition, there is also legal uncertainty involving abortion offense due to the existence of a large number of legal sources or references to articles that regulate abortion offenses. In order for victims of rape and medical emergencies not to be considered ascriminals, the provisions in the Criminal Code and the Health Law must be uniformedto complement each other.